(untitled) (American Journal of Management, 2021)
In response to a rising interest in the connection between innovation and firm performance, this paper examines the body of research on this link and takes a closer look into the influences on innovation, firm performance or both. The basis for this study is a bibliometric analysis of 3,462 scientific publications. We identified 27 innovation domains with an influence on firm performance, showed the rising interest in the topic and found that most types of innovation have a positive impact on firm performance. We provide an overview of which indicators researchers used to measure innovativeness and firm performance and what methods they used to establish the link between the two. Additionally, we stress the importance of sustainable innovation and show that these also positively influence firm performance. In the end, we structure all research fronts into three different groups and based on that, develop a framework that visualizes research on innovation and firm performances.